Hydrolysates of mare's milk proteins. Immunochemical and physico-chemical characteristics - E. S. Semenova; E. S. Simonenko; S. V. Simonenko; S. N. Zorin; V. K. Mazo (Пищевые системы)
In recent years, the attention of specialists has been attracted by a significant increase in allergic diseases, especially among children. Enzymatic hydrolysis with the participation of peptidases is considered the most effective measure to reduce the allergenicity of milk proteins. The study of the features of protein proteolysis by various enzymes, aimed at establishing optimal process parameters, is the subject of research in the production of hydrolysates with specified properties: a certain peptide and amino acid profile, reduced antigenic properties. At the same time, for a correct preclinical assessment of the safety and potential effectiveness of specialized food products, it is not enough only to determine the molecular weight distribution of peptide fractions in the composition. A necessary additional and informative indicator of reducing the potential allergenicity of the hydrolysate is the degree of preservation of the antigenic properties of the initial protein (residual antigenicity), determined by immunochemical methods. The preparation and subsequent comprehensive assessment of enzymatic hydrolysates of mare's milk proteins is of considerable interest, since, according to the results of clinical studies, it was suggested that upon allergy to cow's milk proteins mare's milk can be considered hypoallergenic. The purpose of this work was to obtain enzymatic hydrolysates of mare's milk proteins using domestic enzymes and their further physico-chemical and immunochemical characteristics. The object of the study was mare's milk protein obtained from skimmed mare's milk powder as a protein substrate. Two samples of enzymes from various manufacturers of the Russian Federation were used in the work. The results of the conducted studies show that the peptide profiles of hydrolysates vary greatly depending on the enzyme used, however, the multiplicity of antigenicity reduction practically does not depend on the nature of the enzyme, and does not depend on an increase in the enzyme/substrate ratio. The peptide profile and the multiplicity of reducing the antigenicity of hydrolysates of mare's milk proteins are influenced by ultrafiltration treatment of the obtained hydrolysates, which allows reducing the content of antigenic structures in the final product by several orders of magnitude.